Sufficiently Well Informed and Seriously Concerned? European Union Policy Responses to Marginalisation, Structural Racism, and Institutionalised Exclusion in Early Childhood - Urban, Mathias (Alberta Journal of Educational Research, 2016)
Throughout the European Union, children from marginalised communities experience an appalling reality of poverty, exclusion, discrimination, and racism. Growing up in poverty and social exclusion shapes the reality of the lived experience for an increasing number of children in one of the wealthiest regions of the world. In the UK, a member of the G7, a significant number of children suffer from hunger, malnutrition, and cold (Lansley & Mack, 2015) while the government has abandoned child poverty reduction targets; in Croatia, a recent accession to the EU, “it is normal that Roma children are mostly sick,” according to a recently published report (Šikić-Mićanović, Ivatts, Vojak, & Geiger-Zeman, 2015, p. x). Rather than examining the situation in specific countries, in this paper I undertake a critical inquiry into policy approaches and responses to inequality at the level of the European Union–including the EU Framework for National Roma Integration Strategies–with a specific focus on early childhood education, care, and development. However, while the policies put in place by the European Union have to be welcomed, they represent only one aspect of a complex and often contradictory picture. Perspectives from professionals and activists working “on the ground” are necessary to complement the official picture; they will be presented and discussed in order to identify systemic challenges. I conclude by making the case for a radical systemic turn in EU early childhood policies and for learning with and from experiences in so-called developing countries as a way forward to address these challenges. Dans l’ensemble de l’Union européenne, les enfants de communautés marginalisées affrontent une réalité épouvantable caractérisée par la pauvreté, l’exclusion, la discrimination et le racisme. Grandir dans la pauvreté et l’exclusion sociale façonne le vécu d’un nombre croissant d’enfants dans une des régions les plus riches du monde. Au Royaume-Uni, état membre du G7, un nombre significatif d’enfants souffrent de la faim, de malnutrition et du froid (Lansley & Mack, 2015) et pourtant, le gouvernement a abandonné ses objectifs de réduction de la pauvreté chez les enfants. En Croatie, dont l’adhésion à l’Union européenne est récente, et selon un rapport publié récemment (Šikić-Mićanović, Ivatts, Vojak, & Geiger-Zeman, 2015, p. x) «il est normal que les enfants roms soient surtout malades ». Plutôt que d’examiner la situation dans des pays spécifiques, j’adopte une enquête critique des approches et des réponses politiques face à l’inégalité à l’échelle de l’Union européenne, y compris le cadre de l’UE pour les stratégies nationales d'intégration des Roms, et en me penchant plus particulièrement sur l’éducation, les soins et le développement de la petite enfance. Toutefois, si les politiques mises en place par l’Union européenne doivent être bien accueillies, elles ne représentent qu’un aspect d’un ensemble complexe et souvent contradictoire. Les perspectives de professionnels et de militants œuvrant « sur le terrain » sont nécessaires pour compléter le tableau officiel, et elles seront présentées et discutées de sorte à identifier des problèmes systémiques. Je conclus en plaidant en faveur d’un virage systémique et radical dans les politiques de l’UE sur la petite enfance, et en conseillant que l’on s’inspire des expériences dans les pays dits en développement pour faire face à ces défis.